PENGARUH PEMBERIAN KALSIUM HIDROKSIDA (Ca(OH)2) PADA BUDIDAYA UDANG VANAME (Litopenaeus vannamei) AIR TAWAR - Scabra, Andre Rachmat; Fatimah, Syifa; Cokrowati, Nunik (Universitas Teuku Umar, 2024)
One of Indonesian aquaculture superior commodities is vannamei shrimp. The problems faced by freshwater vannamei shrimp farmers is that the shrimp growth is not optimal at 0 ppt salinity. Regarding shrimp survival, the crucial minerals needed are calcium (Ca), potassium (K), and magnesium (Mg). Calcium is able to increase shrimp skin calcium levels and the length of molting cycle, as well as for the growth of shrimp biomass and an increase in dissolved calcium can lead to an increase in pH. This research utilized calcium hydroxide Ca(OH)2, and was conducted for 45 days. The results showed that the highest SR value at P2 was 73.33%. The highest specific weight growth value was found in P3 as much as 6.21%/ day, and the highest specific length rate was found in P3 as much as 2.66%/ day. The highest coefficient of variance in weight was found in P2 with 46.3%, and the highest coefficient of variation in length was found in P2 with 12.88%. The best FCR value was found in P3 with 0.48. Therefore, adding Ca (OH)2 could increase the growth of vannamei shrimp in freshwater.